Bioactive Compounds of Agro-Industrial By-Products: Current Trends, Recovery, and Possible Utilization - Ramesh Kumar Saini; Mohammad Imtiyaj Khan; Vikas Kumar; Xiaomin Shang; Ji-Ho Lee; Eun-Young Ko (Antioxidants)
Domestic food waste and agro-industrial by-products (AIBPs) occurring throughout the food chain, including production, processing, and storage, have become a global sustainability concern. Interestingly, this waste and these by-products contain a significant amount of commercially vital bioactive compounds, including polyphenols and carotenoids. Remarkably, discarded by-products such as fruit and vegetable peels contain more bioactive compounds than edible pulp. Thus, valorizing this waste and these by-products for commercially vital bioactive products can solve their disposal problems and help alleviate climate change crises. Additionally, it can generate surplus revenue, significantly improving food production and processing economics. Interestingly, several bioactive extracts derived from citrus peel, carrot pomace, olive leaf, and grape seed are commercially available, highlighting the importance of agro-food waste and by-product valorization. Considering this background information, this review aims to provide holistic information on major AIBPs; recovery methods of bioactive compounds focusing on polyphenols, carotenoids, oligosaccharides, and pectin; microencapsulation of isolated bioactive for enhanced physical, chemical, and biological properties; and their commercial application. In addition, green extraction methods are discussed, which have several advantages over conventional extraction. The concept of the circular bio-economy approach, challenges in waste valorization, and future perspective are also discussed.